Gibbs’ cycle review. Emotions as a part of the cycle: english - Galli, Fabio; New, Karl J. (e-Motion: Revista de Educación, Motricidad e Investigación, 2022)
The Gibbs’ cycle, used in reflective practice, is a tool for self-reflection, mental wellbeing monitoring, academic learning and teaching activities, personal and professional development. It is structured in six phases: description, feelings, evaluation, conclusions, and action plan. Considering well-being and mental health as fundamental players in development paths (academic, professional, human), it becomes important to consider emotions in a new structure of the Gibbs’ model. The narrative review is based on the observation of twenty manuscripts, in which the consideration and analysis of emotions in the reflective cycle was sought.